Analysis of Social Networks in Informal Solid Waste Collection and Recycling Enterprise in Makurdi and Lafia Township of North Central Nigeria - Kwaghsende, Dr. Felix K.; Ajene, Ajene Adam (IJRDO-Journal of Applied Science, 2018)
Literature has shown that a main feature of the informal sector economic enterprise is the use of informal social network to drive enterprise. However, we do not know whether the networks used are the same in informal solid waste collection and recycling activities and how they influence informal solid waste recycling activities in Nigerian cities. The study analysed social network in informal solid waste collection and recycling enterprise in Makurdi and Lafia Township, North central Nigeria. Questionnaire and interview guide were used to collect data on social network variables and its influence on informal recycling enterprise. Cluster and purposive samplings were applied to select and administer questionnaire to 770 respondents waste pickers using the existing spatial structures from the towns while chairmen of the waste dealers associations were interviewed. Data collected was analysed using descriptive and analytical statistics, namely mean, standard deviation, chi square and phi coefficient. The study found that social networks that sustains the enterprise includes ties with house owners, ethnic affinities, partnership with private business institutions and the role played by waste dealers associations in giving security tips, providing financial assistance to members among others. The chi square analysis shows statistically significant relationship between social network and level of involvement in informal activities (p= 0.000, p<0.05).Phi coefficient analysis also shows positive relationship (Phi= .326). Policy implications of the network include their use as collateral for members for credit facilities for poverty alleviation and to engage the state for other capacity building programmes. The study recommended for policy measures that could foster partnership with the recycling workers and contribute to expand the enterprise for more livelihood opportunities and mutual benefits between government and the recycling workers.